Accelerated HF‐rTMS Protocol has a Rate‐Dependent Effect on dACC Activation in Alcohol‐Dependent Patients: An Open‐Label Feasibility Study. (January 2016) - Herremans, Sarah C.; De Raedt, Rudi; Van Schuerbeek, Peter; Marinazzo, Daniele; Matthys, Frieda; De Mey, Johan; Baeken, Chris
Abstract : Background: The application of accelerated high‐frequency (HF) repetitive transcranial magnetic stimulation (rTMS) could be a potential treatment option for alcohol‐dependent patients and may result in a faster clinical response. In this open‐label HF‐rTMS feasibility study, we wanted to replicate previous findings of baseline brain activation as a predictor of relapse, and to evaluate how this intervention influences the relapse neurocircuit of "treatment‐seeking" alcohol‐dependent patients, by means of functional magnetic resonance imaging (fMRI) cue‐exposure paradigms. Because relapsing patients have a diminished resilience of the emotion regulation/cognitive control system, before HF‐rTMS treatment, we expected lower neuronal activation of especially the ventromedial prefrontal cortex and anterior cingulate cortex (ACC) during the presentation of alcohol‐related cues in these patients. The relapse neurocircuit should be modified after accelerated HF‐rTMS treatment, only in those patients who did not relapse. Methods: After being administered a single sham‐controlled HF‐rTMS session (20 Hz to 110% motor threshold), 19 alcohol‐dependent patients received an accelerated HF‐rTMS protocol, consisting of 14 right dorsolateral prefrontal cortical sessions spread over 3 days. Before and after stimulation, during fMRI patients were confronted with a block and an event‐related alcoholic cue‐exposure paradigm. Relapse was defined as the consumption of any amount of alcohol within 4 weeks after the stimulation. A region of interest analysis was performed to evaluate how HF‐rTMS exerts its effect. Results: After 4 weeks, 13 of 19 patients had already consumed alcohol. When abstainers were compared to patients who had relapsed, we found higher dorsal ACC (dACC) activation at baseline, but only during the blocked cue‐exposure paradigm. The effects of HF‐rTMS on dACC blood oxygen level‐dependent response were negatively correlated with the baseline dACC activation. Due to susceptibility artifacts located at the ventral cortical aspects in 6 of our participants, reliable data were only obtained for the ACC. Conclusions: Our data indicate that higher baseline dACC activation may serve as a protective mechanism regarding relapse. For the first time, it is demonstrated that accelerated HF‐rTMS treatment influences dACC activation in a rate‐dependent manner: the lower the baseline dACC activation, the more dACC activity was increased after HF‐rTMS treatment. Abstract : Dorsal anterior cingulate cortex (dACC) activation during an alcohol‐related cue‐exposure is influenced by accelerated high‐frequency (HF) repetitive transcranial magnetic stimulation (rTMS) in a rate‐dependent manner: the lower the baseline dACC activation, the more dACC activity was increased after HF‐rTMS treatment. Although higher baseline dACC activation may be protective against future alcohol relapse, the limited increase of dACC activation in patients, who relatively fast relapse, suggests that the accelerated stimulation protocol lacks sufficient clinical impact.